"Sex hormone independent associations between insulin resistance and thyroid status –a gender based biochemical study on clinically euthyroid non-obese, overweight and obese type 2 diabetics''. Issue 3 (May 2019) - Jayanthi, Rajendran; Srinivasan, Abu Raghavan
Abstract: Aim: Studies indicate that type 2 diabetes mellitus (T2DM) might contribute to the development of thyroid disorders (TD). However, few gender based reports are available describing therelationship between T2DM and TD in clinically euthyroid, anthropometry specified groups of type 2 diabetics. The aim of this study was to relategender based biochemical changes in anthropometry specified, clinically euthyroid type 2 diabetics. Methodology: The study was carried out on clinically euthyroid type 2 diabetics (male n = 269; female n = 301) at a tertiary health care unit in Pondicherry, South India. Three groups were segregatedbased on Body mass Index: 153 non-obese type 2 diabetics (BMI = 18.5–24.99), 291 overweight type 2 diabetics (BMI = 25–29.99) and 126 obese type 2 diabetics (BMI ≥ 30). Biochemical parameters included glycated hemoglobin, insulin resistance, Cortisol and Thyroid profile. Results: The study had included clinically euthyroid type 2 diabetics (52.8% females and 47.2% males). Statistically significant associationsweredifferently observed between insulin resistance (dependent variable) andother independent variables, irrespective of sex hormone status. Total protein was negatively related in non -obese male type 2 diabetics (R = 0.780); Triiodothyronine was inversely associated in overweight males, whereas cortisol and the divalent cations (Zinc and Magnesium) depicted positive association (R = 0.555) in the same group (overweight), butcortisol in non -obese female type 2 diabeticswas negative (R = 0.742); Glycated hemoglobin and calcium exhibited positive relationshipin obese type 2 female diabetics (R = 0.771).. Conclusion: Our study has revealed distinctive relationship between T2DM and TD in the anthropometry specified, clinically euthyroid and gender based type 2 diabetics, independent of the sex hormones.